Managing employee engagement with cross-cultural leadership style (case study at united nations development programme indonesia) - Yusuf Musa, Muhammad; Febriansyah, Hary (The Indonesian Journal of Business Administration, 2018)
Abstract - United Nations Development Programme (UNDP) Indonesia is an international organization work as one of the representative program by United Nations. UNDP Indonesia was founded on 22 November 1965 in Jakarta together with the head office. United Nations Development Programme Indonesia is the international organization with multicultural diversity. The employee including the managers and the staff at United Nations Development Programme Indonesia working based on the work culture inside the organization. Multicultural diversity at United Nations Development Programme Indonesia make the managers used to think how to get engage with the staff that have cultural diversity. Managing employee engagement with cross cultural leadership style would be a challenge for the managers, and the staff support the manager job together to reach the objectives. This research using qualitative method to gain the data more complex. In this research, there are eight of UNDP Indonesia employees that supporting as the informants, including two expatriates manager, two local managers, two local staffs, and two expatriates staff. The recommendation has been made by the research choosing the leadership style that engage with United Nations Development Programme Indonesia staff. Keyword: employee engagement, cross-cultural leadership, leadership style